Die Sammlung Fer - Sauer, Christel; Maenz, Paul (Köln : Verlag Gerd de Vries, 1983)
Adamski ; Albers ; Andre ; Anselmo ; Antes ; Art & Language ; Barfuss ; Barry ; Beuys ; Bissier ; Bömmels ; Boetti ; Boyle ; Büttner ; Buren ; Calderara ; Camargo ; Chia ; Clemente ; Cucchi ; Dahn ; Daniels ; Darboven ; Dekkers ; De Maria ; Dibbets ; Disler ; Dokoupil ; Fabro ; Fetting ; etc.
boek